2017
DOI: 10.1016/j.chiabu.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a predictor of posttraumatic stress symptoms and externalizing behavior problems in sexually abused children

Abstract: Despite the proliferation of studies documenting outcomes in sexually abused victims, gender differences remain understudied. The bulk of studies have relied on retrospective samples of adults with insufficient representation of male victims to explore gender specificities. This study examined differential outcomes among boy and girl victims of sexual abuse. A predictive model of outcomes including abuse characteristics and sense of guilt as mediators was proposed. Path analysis was conducted with a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 35 publications
5
35
1
3
Order By: Relevance
“…While some studies found that females are more sensitive to CM (McGee et al, 1997; MacMillan et al, 2001; Lansford et al, 2002; Banyard et al, 2004; Fletcher, 2009; Herringa et al, 2013b), others maintain that males are more sensitive (Hibbard et al, 1990; Garnefski and Diekstra, 1997; McGloin and Widom, 2001; De Bellis and Keshavan, 2003; Bergen et al, 2004; Zeanah et al, 2009; Coohey, 2010; Crozier et al, 2014). A third group of studies proposed a more nuanced and complex relationship between sex and CM, suggesting that the outcome depends on the type of maltreatment, genetic vulnerability, the specific circuit involved, and the developmental stage when the outcomes are assessed (Darves-Bornoz et al, 1998; Gershon et al, 2008; Keyes et al, 2012; Bale and Epperson, 2015; Humphreys et al, 2015; Teicher and Samson, 2016; Gauthier-Duchesne et al, 2017). See also Supplementary Table S1.…”
Section: Modereating Effects Of Sex In Clinical and Preclinical Studiesmentioning
confidence: 99%
“…While some studies found that females are more sensitive to CM (McGee et al, 1997; MacMillan et al, 2001; Lansford et al, 2002; Banyard et al, 2004; Fletcher, 2009; Herringa et al, 2013b), others maintain that males are more sensitive (Hibbard et al, 1990; Garnefski and Diekstra, 1997; McGloin and Widom, 2001; De Bellis and Keshavan, 2003; Bergen et al, 2004; Zeanah et al, 2009; Coohey, 2010; Crozier et al, 2014). A third group of studies proposed a more nuanced and complex relationship between sex and CM, suggesting that the outcome depends on the type of maltreatment, genetic vulnerability, the specific circuit involved, and the developmental stage when the outcomes are assessed (Darves-Bornoz et al, 1998; Gershon et al, 2008; Keyes et al, 2012; Bale and Epperson, 2015; Humphreys et al, 2015; Teicher and Samson, 2016; Gauthier-Duchesne et al, 2017). See also Supplementary Table S1.…”
Section: Modereating Effects Of Sex In Clinical and Preclinical Studiesmentioning
confidence: 99%
“…A major obstacle in clarifying some of these clinical observations is the over reliance on subjective reports about sensitive and personal information usually obtained by a complete stranger 8 , 9 , 15 . In this regard, the recent use of functional imaging provides an important and promising objective tool to study the effects of childhood adversity on brain function and connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…As defined by World Health Organization gender violence is 'the greatest public health issue and violation of human rights in the world; it is a violation of a person's physical and mental integrity (WHO 2014). SA is a traumatic life event in which the negative outcomes increase with increasing severity of abuse including physical maltreatment (McCauley et al 1997) such us lacerations, fractures, genital mutilation, sexually transmitted diseases (Lacey 1990), gynecologic disorders (Walling et al 1994;Golding et al 1998) unwanted or pathological pregnancies (Murphy et al 2001), depression (Wise et al 2001), eating disorders (Goodwin et al 2003), self-destructive behaviours (Alix et al 2017) genito-urinary and sexual disorders (Vella et al 2015), post-traumatic stress disorders (Kendler et al 2000;MacMillan et al 2001;Sprinter et al 2007;Jonas et al 2011;Gauthier-Duchesne et al 2017;Bottomley et al 1999). Internationally, different approaches are taken to the collection of forensic evidence and to the clinical and psychological assessment of alleged victims Berry et al 2014).…”
Section: Introductionmentioning
confidence: 99%